Hyperbaric oxygen therapy: when pressure is good for diabetic foot ulcers. (1st March 2022) - Lalieu, Rutger; Raap, René Bol; van Hulst, Rob
Abstract : The diabetic foot ulcer (DFU) as a common complication of diabetes. Even with adequate treatment, up to 35% of these ulcers do not heal. This is due to the effect of aging, repeated ischemia-reperfusion (IR) injury, bacterial colonisation of the wound and chronic hypoxia. All wound-healing processes are highly dependent on oxygen, so hyperbaric oxygen therapy (HBOT) can be employed to improve wound healing and correct the four pathophysiological factors for chronic wounds. It is, in fact, internationally recognised as a treatment option for non-healing DFUs. Several trials and systematic reviews have been performed on its efficacy, which show a positive trend towards increased wound healing and reduced amputation risk. Some controversy exists due to contradictory results in these studies, which may be due to grouping patients with and without peripheral arterial occlusive disease (PAOD) together. Side effects are usually mild and transient, and the treatment is considered safe.